Blockchain-Based Tokenized Storage Incentives: Revolutionizing Decentralized Object Storage - Ankit Gupta, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents an innovative approach to decentralized object storage that combines blockchain technology, distributed hash tables (DHTs), and advanced cryptographic techniques. The proposed system addresses the limitations of traditional centralized storage infrastructures by implementing a token-based incentive mechanism that encourages network participation while ensuring data security and availability. By integrating proof-of-storage consensus mechanisms consensus mechanisms, homomorphic encryption, and erasure coding, the architecture demonstrates superior fault tolerance and operational efficiency. The system's implementation showcases significant improvements in resource utilization, cost reduction, and environmental sustainability compared to conventional cloud storage solutions. Furthermore, the framework incorporates robust data sovereignty protections and compliance mechanisms, making it suitable for enterprise deployments and small-medium enterprises alike.
Keywords: Blockchain integration; Decentralized storage systems; Distributed hash tables; Homomorphic encryption; Tokenized incentives